المنهج بين الخصوصية و الكونية عند محمد مفتاح - عبلة, بن منصور; شراف, شناف (جامعة الوادي - University of Eloued, 2022)
نطمح من خلال هذه الدراسة إلى تحقيق هدفين: الأول تسليط الضوء على مؤلفات "محمد مفتاح"، الذي يعتبر من النقاد البارزين في الساحة النقدية العربية المعاصرة، وتظهر قيمة هذا الهدف في محاولة البحث في المناهج التي اعتمدها "مفتاح"على مستوى التنظير والتطبيق. أما الهدف الثاني فهو محاولة الكشف عن الخلفيات الابستمولوجية وكذا مختلف الحقول العلمية والمعرفية التي استقدم منها مفتاح مختلف الآليات والمفاهيم التي اعتمد عليها لاكتشاف خبايا النصوص التراثية والمعاصرة، وأظهرت نتائج هذه الدراسة مدى كونية الممارسة المنهجية عند مفتاح من حيث التنوع، وكذا خصوصية هذه المناهج من حيث الدقة والانتقائية في تطبيقها. Through this study, we intend to achieve two objectives: the first one is to shed light on the works of Mohammed Meftah, who is considered to be one of the most prominent contemporary Arab critics in his field, and that by trying to investigate the methodologies he adopted. The second one is the attempt to expore the epistemological backgrounds, as well as the various scientific and cognitive fields from which the key to the numerous mechanisms and concepts relied upon to discover text crypts, the results of this study showed the universality of Mefteh’s methodological practice in terms of diversity, and the specificity of these curriculum in terms of accuracy and selectivity in their application.
مقال
Keywords: منهج ; خصوصية ; كونية ; محمد مفتاح; curriculum ; specificity ; universality ; Mohamed Meftah